Improving the sense of city belonging among migrant elderly following family from an elderly service perspective: a cross-sectional study - Meijie Chu; Chun-Yang Lee; Lamu Suona; Min Gao; Tianmu Chen; Shuoxun Zhang; Yi-Chen Chiang (BMC, 2022)
Abstract Background The migrant elderly following family (MEFF), who migrates to new community to reunite with families, may face challenges of city integration and belonging. This study aims to explore from an elderly service perspective how to improve the sense of city belonging for MEFFs with and without hypertension/diabetes conditions. Methods Data were derived from the 2017 China Migrants Dynamic Survey and China National Statistical Yearbooks in 2017. The study included 882 MEFFs with hypertension or diabetes and 1266 MEFFs without hypertension and diabetes. Hierarchical linear modeling was applied to analyze the effects of individual and provincial elderly services on sense of city belonging among the MEFF with and without hypertension/diabetes. Results The MEFFs with hypertension or diabetes exhibited a greater sense of city belonging when they were familiar with a wider range of health education topics (γ = 0.05, p = 0.033) and were in those provinces with a greater number of licensed doctors (γ = 0.39, p < 0.001) and hospitals (p = 0.042). For those MEFFs without hypertension or diabetes, social security cards (γ = 0.57, p < 0.001) and awareness of a wider range of health education topics (γ = 0.07, p = 0.018) may help to improve their sense of city belonging. Conclusion This study calls for strengthening the accessibility in inclusive elderly services, and minimizing or even eliminating the inequality in elderly services at the individual and provincial levels to increase sense of city belonging among the MEFFs. For the MEFFs with hypertension or diabetes, health managers should focus on improving health information dissemination and increasing the number of doctors per 1000 people as well as and the number of hospitals to enhance the sense of city belonging. Moreover, the government should strengthen social security and health education to facilitate the adaptation and integration of MEFFs without hypertension and diabetes into the host city.